Pelatihan Pengelolaan Emosi Berbasis Nilai Kristiani dan Peningkatan Kendali Diri Anak: (Studi pada Jemaat GPM Wonreli–Kisar) - Sestrix C. Rahabav (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the persistent difficulty elementary school-aged children have in controlling their emotions and behavior in social situations, particularly within the context of church community development. The study aimed to examine the effect of Christian values-based emotion management training on improving children's self-control. The study used a quantitative approach with a quasi-experimental one-group pretest-posttest design on 30 children aged 7–12 years at the GPM Wonreli–Kisar Congregation. The intervention was implemented over four days through activities involving emotion recognition, value reflection, emotion regulation training, and social simulations. Data were collected using a self-control scale and analyzed using paired-difference tests and effect size calculations. The results showed a significant increase in self-control scores after the training, with the largest changes in rule compliance and impulse control, and a more moderate increase in resilience to frustration. The effect size indicates a strong practical impact of the changes. These findings indicate that training that integrates social experiences and value reflection can facilitate the shift in behavioral control from external control to internal awareness. Practically, this research provides a basis for developing a community-based child development program that emphasizes not only discipline but also the understanding of values ​​in character formation and self-regulation.